Secondary Hypogonadism in Recurrent Adamantinomatous Craniopharyngioma: Fertility Evaluation and Management - Adeputri Tanesha Idhayu; Tri Juli Edi Tarigan; Em Yunir; Setyo Widi Nugroho; Eka Susanto (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Craniopharyngioma is an intracranial tumor with pituitary hormone deficiencies and affects 40% of gonadotropins deficiency. Gonadotropin deficiency causes secondary hypogonadism and male infertility which need to investigation for male infertility therapy options. A 22-year-old man presented with history of intermittent headaches, visual impairment, mild left- side hemiparesis, and developed erectile dysfunction. On clinical examination, there was abnormal penile and testicular size. The radiological examination showed a solid intrasellar mass with cystic lesion. The histological diagnosis was adamantinoma Tous craniopharyngioma. The hormonal evaluation showed low testosterone level, LH and FSH, and semen analysis showed azoospermia. The human chorionic gonadotropin stimulation test showed testosterone increase times from baseline, but evaluation semen test remained azoospermia. Craniopharyngioma morbidity is associated with tumor related and or treatment-related risk factors such as hormone deficiencies. Pituitary hormone deficiencies have been reported in 54–100% of patients that affect secretion of growth hormone, gonadotropin, TSH and ACTH. Gonadotropin deficiency associated with infertility in men. In this case, gonadotropin deficiency was due to the tumor because the symptoms had developed before surgery. Hypogonadism in this case occurs after puberty and he willing to have offspring. The hormonal therapy is effective in restoring spermatogenesis relates to the regulatory of the hypothalamic pituitary gonadal axis. The administration of HCG alone or combined with FSH, restores spermatogenesis of patients with hypogonadotropic hypogonadism, with reported pregnancy rates of up to 65%. Gonadotropin stimulation therapy will be planned after ruling out seminal tract obstruction and testicular fibrosis. Infertility in secondary hypogonadism can be managed with hormone therapy, but a complete investigation is required before starting treatment to determine therapy options.